2002
DOI: 10.2527/2002.8082017x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of selection for ultrasound intramuscular fat percentage in Angus bulls on carcass traits of progeny

Abstract: Angus bulls (n = 20) from three pure-bred herds in Georgia were acquired to determine the impact of selecting sires based on phenotypic yearling ultrasound intramuscular fat percentage (UIMF) or UIMF EPD on marbling score of steer progeny. Each year in each herd, pairs of bulls were selected to create large differences based on their age adjusted phenotypic yearling UIMF measurements. The average UIMF, weighted by number of progeny per sire, was 3.75% (SD = 1.10%) and 1.70% (SD = 0.53%) for high UIMF (HU) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0
6

Year Published

2004
2004
2010
2010

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 15 publications
2
27
0
6
Order By: Relevance
“…However, marbling is affected by breed (Zembayashi, 1994), fattening period (Lengyel et al, 2003) and diet (Andrae et al, 2001). In addition, animal category can also influence marbling content, despite the fact that yearling bulls have much lower levels of intramuscular fat than finished cattle (steers and heifers), sires selected for marbling content based on their own scanned marbling score produce steer progeny with greater amounts of marbling (Sapp et al, 2002). Therefore, marbling might be relevant for RFI determination under situations where the factors affecting marbling exhibit a greater variation than that observed in the present study.…”
Section: Discussionmentioning
confidence: 97%
“…However, marbling is affected by breed (Zembayashi, 1994), fattening period (Lengyel et al, 2003) and diet (Andrae et al, 2001). In addition, animal category can also influence marbling content, despite the fact that yearling bulls have much lower levels of intramuscular fat than finished cattle (steers and heifers), sires selected for marbling content based on their own scanned marbling score produce steer progeny with greater amounts of marbling (Sapp et al, 2002). Therefore, marbling might be relevant for RFI determination under situations where the factors affecting marbling exhibit a greater variation than that observed in the present study.…”
Section: Discussionmentioning
confidence: 97%
“…As marbling score in these animals is genetically highly correlated with muscle lipid content (r G 5 0.91), selection based on the former may lead to a correlated improvement in tenderness (for review, see Hocquette et al, 2006). This relationship explains most of the efforts dedicated to the development of live scanning for IMF content as a selection tool in the United States and Australia (Reverter et al, Intramuscular fat content in meat-producing animals 2000; Hassen et al, 2001;Sapp et al, 2002). However, as marbling is positively genetically correlated to the carcass fatness, the undesirable side effects of selection on the basis of IMF content or marbling are often the increase in carcass fatness.…”
Section: Genetic and Genomic Markers Of Imf Contentmentioning
confidence: 99%
“…The heritability for USIMF in yearlings has been reported varying from 0.23 (Devitt and Wilton, 2001) to 0.50 (Hassen et al, 2003). Sapp et al (2002) reported higher marbling and quality grade in carcasses of offspring from Angus bulls selected for high USIMF. This was in accordance with Devitt and Wilton (2001), who estimated a genetic correlation (r g ) of 0.80 between steer carcass marbling score and bull USIMF based on half-sib relationships.…”
Section: Introductionmentioning
confidence: 95%